Create a chat application with PHP and Ajax - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"In this course the user will learn to build their own, fully functional chat application for websites using PHP and Ajax. A basic knowledge of PHP and Ajax is recommended for this course, but both beginners and experienced web developers will benefit from this concise set of tutorials. The instructor will also be using some basic JavaScript, MySQL and jQuery. Over 9 lectures and 59 mins of content."--Resource description page.
Description based on online resource; title from resource description page (Safari, viewed November 19, 2014).
Keywords: Online chat groups -- Computer programs; PHP (Computer program language); Ajax (Web site development technology); Programming languages (Electronic computers); Web site development; Electronic books